(untitled) (Estudios humanísticos. Geografía, historia y arte, 1989)
The Count of Lemos, one of the most important Galician lineages, will let to fill his enormous weight on the "berciana" society in the fifteen century as a result of the acquisition of territorial and jurisdictional basis in this country which has allow him to consolidate his position amongst the Galician-Leonese nobility. His inheritance, absolutely shaped in the middle of the XVth century, was mainly placed in the "Bierzo Bajo", scene where important social conflicts will take place. The "antiseñorial" resistance (1467-1469) with the growth of "hermandades" in the "Bierzo" and the confrontation against the Count of Lemos can be underlined. This conflicts are closely joined with the "irmandiño" movement developed at the same time in Galicia.